IID water information system -- irrigation database principles and management - Thoreson, Bryan, author; Divine, Anisa, author; Archer, Mike, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1998)
The Imperial Irrigation District (IID) and the Metropolitan Water District of Southern California (MWD) entered into a pioneering water transfer agreement in 1988. MWD was to finance water conservation programs in the IID in return for the transfer of the conserved water volume each year for 35 years. A requirement of the agreement was that the water conserved be verified. In 1993, the authors spearheaded collection of conservation verification data using the WCC SCADA system. As measurement structures and data collection equipment were installed and calibrated, data collection began. Initial examination of the data showed that certain types of data errors occurred repeatedly. A Fortran program, developed to incorporate these checks, was used in conjunction with spreadsheets to achieve a high level of consistent, automated data quality control. Meanwhile, other IID departments were collecting data using Stevens Charts and data loggers, with the logger data being processed in a spreadsheet. Manual quality control was performed on both types of data. The IID/MWD program began developing a Water Information System (WIS) incorporating daily quality control operations and a data storage warehouse function for site-specific, time-series data related to the flow of water through IID's irrigation and drainage system. The WIS also provides an audit trail of the data elements as they flow through the quality control operation. Once a month, graphs of the data are printed, checked for final quality control, and archived as hard copy. A Processed Flow Data document is published annually, and a Users Manual is updated regularly to be current with procedural changes. In this paper, the authors describe the principles they have incorporated and the lessons they have learned during the process of setting up the irrigation flow database. Primary among these insights are: 1) the value of keeping all data in a centralized database eliminating duplication and ensuring that all analysts use the same data, and 2) keeping all data entry and manual data quality control decentralized so that data quality control is done by those who know the data best.
USCID 14th technical conference
Not digitized by CSUL Digital Services.
Presented at Contemporary challenges for irrigation and drainage: proceedings from the USCID 14th technical conference on irrigation, drainage and flood control held on June 3-6, 1998 in Phoenix, Arizona.